The Speech Act of Request and Refusal in English as a Foreign Language: Hotel Front Desk’s Linguistic Politeness - Yunita, Widia; Wahyudi, Riki (Elsya : Journal of English Language Studies, 2020)
The subject matter discussed in this paper is how hotel front desk receptionists handle requests and refusals in their interactions with customers when they use English as a Foreign Language (EFL). The method of this research is descriptive with a qualitative approach, examining the interactions of front desk employees who work at Hotel Surya Duri, Indonesia. The sample consists of seven people who were given a discourse completion test which questioned them on how they deal with five different scenarios of customer requests and refusals. Results showed that employees perform independent research largely on how to deal with customer requests, but overall do not adequately master how to engage with foreign customer requests and refusals in EFL. This study suggests that concerned parties may benefit training current employees in foreign language communication training.